2015
DOI: 10.21273/hortsci.50.9.1370
|View full text |Cite
|
Sign up to set email alerts
|

Paclobutrazol or Ancymidol Effects on Postharvest Performance of Potted Ornamental Plants and Plugs

Abstract: Effects of paclobutrazol and ancymidol on postharvest performance and growth control of potted sunflower (Helianthus annuus L.), zinnia (Zinnia elegans Jacq.) and marigold (Tagetes erecta L.), petunia (Petunia ×hybrida Vilm.) plugs, respectively, were studied. Paclobutrazol was applied as a drench at 0, 1.0, 2.0, or 4.0 mg of a.i. per 15.2-cm pot for sunflower and 0, 0.5, 1.0, or 2.0 mg per 12.5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
2
18
0
1
Order By: Relevance
“…1 were higher than the control. These results are consistent with those of Ahmad et al (2015) who observed darker green foliage for 'Pacino Gold' potted sunflower treated with 2 to 4 mg/pot paclobutrazol substrate drenches and for Barbosa et al (2008) who reported increased chlorophyll meter measurements with increased paclobutrazol substrate drench rates, peaking between 4 to 6 mg/pot for 'Golden' potted sunflower. Increased foliar chlorophyll content with increasing paclobutrazol rate has been reported in additional plant genera to sunflowers [Helianthus sp.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…1 were higher than the control. These results are consistent with those of Ahmad et al (2015) who observed darker green foliage for 'Pacino Gold' potted sunflower treated with 2 to 4 mg/pot paclobutrazol substrate drenches and for Barbosa et al (2008) who reported increased chlorophyll meter measurements with increased paclobutrazol substrate drench rates, peaking between 4 to 6 mg/pot for 'Golden' potted sunflower. Increased foliar chlorophyll content with increasing paclobutrazol rate has been reported in additional plant genera to sunflowers [Helianthus sp.…”
Section: Discussionsupporting
confidence: 91%
“…2, plants treated with paclobutrazol at 4.0 mg/pot had 27% and 36% reductions in height growth, respectively, compared with the control. Similar results with a substrate drench application of 4 mg/pot paclobutrazol were observed as 26% to 36% shorter plants than the control by Dasoju et al (1998), Whipker and McCall (2000), and Ahmad et al (2015) for potted annual sunflower. Although previous studies observed 20% to 27% shorter plants with a 2 mg/pot drench of paclobutrazol on potted sunflower (Ahmad et al, 2015;Dasoju et al, 1998;Whipker and McCall, 2000;Whipker et al, 2004), the same application method and concentration in this study on swamp sunflower was not different from the control.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…These smaller, sturdier plants allow growers to use bench space more efficiently and help plants to endure shipping and retail handling. In addition, there are other potential benefits of PGRs including improved plant water-use efficiency (Ahmad et al, 2014;Jungklang and Saengnil, 2012) and disease suppression (Hill and Latimer, 2004).…”
mentioning
confidence: 99%